1998
DOI: 10.1017/s0014479798343045
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Growth and Drought Tolerance in Rubber During the Immature Phase in a Dry Subhumid Climate

Abstract: An experiment with the objective of evaluating the performance of 15 clones of rubber (Hevea brasiliensis) was conducted in the Konkan region of Western India. The clones under evaluation were RRII 5, RRII 6, RRII 105, RRII 208, RRII 308, RRIC 52, RRIC 100, RRIC 102, RRIC 105, RRIM 605, PB 260, PB 310, PB 311, PR 255, and PR 261. The region is a trial environment for the crop and experiences more than seven rainless months and severe drought in the summer months. Data on monthly girth growth w ere collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 0 publications
3
28
0
2
Order By: Relevance
“…This subsurface water uptake is necessary to increase stem water potential above a certain threshold to allow bud break . In support, a study in northern India showed girth perimeter increasing several weeks before the first rainfall, possibly indicating rehydration of the tree from deep layer water uptake, associated with bud breaking (Chandrashekar et al, 1998). Furthermore, flushing induced by increasing day-length during the late dry season has been observed in many tropical tree species in monsoon forests around the globe Elliott et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This subsurface water uptake is necessary to increase stem water potential above a certain threshold to allow bud break . In support, a study in northern India showed girth perimeter increasing several weeks before the first rainfall, possibly indicating rehydration of the tree from deep layer water uptake, associated with bud breaking (Chandrashekar et al, 1998). Furthermore, flushing induced by increasing day-length during the late dry season has been observed in many tropical tree species in monsoon forests around the globe Elliott et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
“…However, because of its economic importance, rubber is now cultivated at higher latitudes and altitudes in South America, Southeast Asia and Africa. In these marginally suitable environments (colder and drier), the productive life of rubber, its yield and its growth are reduced (Chandrashekar et al, 1998;Devakumar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have directly compared the extent of growth reduction due to drought between species (e.g., Jarvis and Jarvis 1963;Evans and Etherington 1991;Espigares and Peco 1995;Fernandez and Reynolds 2000). Of the relevant studies of drought effects on growth of woody rainforest plants, most have shown that droughted seedlings, as well as saplings and mature trees, have reduced growth compared to plants under wet conditions (e.g., Unwin and Kriedemann 1990;Fisher et al 1991;Veenendaal et al 1995;Poorter and HayashidaOliver 2000;Ito et al 2000;Chandrashekar et al 1998). Methodological differences and the very limited number of species investigated do not allow comparisons based on the available data.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1980s, rubber research institutions have studied productivity and adaptability of Hevea clones to relatively cold and dry environments (Gururaja Rao et al, 1990;Vijayakumar et al, 1998;Priyadarshan et al, 2001). Clones are now adapted to overcoming dry periods and lower temperatures without important loss of latex yield (Chandrashekar et al, 1998;Rodrigo, 2007). Using new genotypes, rubber plantations have now expanded to 27°N latitude and up to 1100 m in elevation (Priyadarshan et al, 2005), well beyond the native environment of 10°N/S of the equator and 400 m above mean sea level (AMSL) (Priyadarshan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%